2020
DOI: 10.1136/jitc-2019-000291
|View full text |Cite
|
Sign up to set email alerts
|

Granzyme B PET imaging of immune-mediated tumor killing as a tool for understanding immunotherapy response

Abstract: BackgroundCancer immunotherapy research is expanding to include a more robust understanding of the mechanisms of treatment response and resistance. Identification of drivers of pro-tumor and anti-tumor immunity during treatment offers new strategies for effective alternative or combination immunotherapies. Currently, tissue or blood samples are collected and analyzed, then dichotomized based on clinical end points that may occur months or years after tissue is collected. While overall survival is ultimately th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 33 publications
1
28
0
2
Order By: Relevance
“…30 Unexpectedly, we identified the MLNs as a robust offtumor IDO1 site for active immune response monitoring (figures 3 and 4), different from currently known methods that focus on tumor sites (online supplemental table 4). [31][32][33][34][35][36][37][38][39][40][41][42][43][44] These findings enabled us to distinguish l-1MTrp+CPA as a more effective regimen than l-1MTrp+PTX for treating murine B16F10 melanoma (figure 3), simplifying the assessment of immunotherapy effectiveness, and allowing oncologists to rapidly analyze and screen more effective combination regimens on a common platform. Although various studies have indicated that the combination of an IDO1 inhibitor with chemotherapy induces antitumor immunity, which leads to immune-mediated clearance of IDO1-expressing and nonexpressing poorly immunogenic tumors, including melanoma, 1-3 11 19 failed clinical trials with IDO1 inhibitors have set back the development of this approach.…”
Section: C-l-1mtrp Imaging In the Context Of Combinatorial Immunotherapy With Pd-1 And Ctla4 Blockadementioning
confidence: 99%
“…30 Unexpectedly, we identified the MLNs as a robust offtumor IDO1 site for active immune response monitoring (figures 3 and 4), different from currently known methods that focus on tumor sites (online supplemental table 4). [31][32][33][34][35][36][37][38][39][40][41][42][43][44] These findings enabled us to distinguish l-1MTrp+CPA as a more effective regimen than l-1MTrp+PTX for treating murine B16F10 melanoma (figure 3), simplifying the assessment of immunotherapy effectiveness, and allowing oncologists to rapidly analyze and screen more effective combination regimens on a common platform. Although various studies have indicated that the combination of an IDO1 inhibitor with chemotherapy induces antitumor immunity, which leads to immune-mediated clearance of IDO1-expressing and nonexpressing poorly immunogenic tumors, including melanoma, 1-3 11 19 failed clinical trials with IDO1 inhibitors have set back the development of this approach.…”
Section: C-l-1mtrp Imaging In the Context Of Combinatorial Immunotherapy With Pd-1 And Ctla4 Blockadementioning
confidence: 99%
“…[ 81 ] Indeed, granzymeB‐based imaging applications are attracting increasing interest. [ 82 ] A similar approach to detecting antigen‐specific T lymphocytes has been developed by Ploegh et al. [ 83 ] Unlike targeting to Granzyme B, the different peptides provided a variable platform to identify different antigen‐activated T cells.…”
Section: Stratifying Tumor Responsementioning
confidence: 99%
“…A handful of fluorogenic (35)(36)(37), photoacoustic (37), chemiluminescent (29), and PET (28) probes have been developed for imaging gzmB activity or its distribution in vivo. These studies focused on probing gzmB in different preclinical models and have supported gzmB as a reliable biomarker of cytotoxic cell activation in anti-cancer responses (28,38,39).…”
Section: Introductionmentioning
confidence: 99%